Degree of constructed-response interaction in computer-based programmed instruction. - Kritch, Kale M.; Bostow, Darrel E. (Journal of Applied Behavior Analysis)
This investigation evaluated the importance of frequent responding in computer-based programmed instruction. Instructional computer programs that taught the use of an authoring language were administered to 155 undergraduate college students. One group experienced frequent (dense) situations requiring them to supply key components of the subject taught. A second group experienced half as many response requirements, and a third “passive” group simply tapped any key to progress. To control for time in contact with presentations, individuals in a fourth group were yoked to the members of the high-density requirement group. Statistically significant differences on both posttest and application performances indicated that students who experienced the high density of overt response contingencies scored the best and the passive group score the worst. The yoked control revealed that time on task alone could not account for the superior performance of students in the high-density group. Results suggest that inclusion of a high rate of constructed-response contingencies within instructional computer programs increases performance. Reprinted by permission of the publisher.